Design and Build of Electronic-Based Cessna 172 Aircraft Fuel System Simulator - Setijono, Eko; Reza, Reza; Wulansari, Ajeng (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Airplanes need a system that can control the distribution of fuel in each operation so that the resulting fuel supply is stable. Based on the research results of Edgar Dale (1969), 90% of a person has the ability to absorb objects of knowledge by doing.This final project discusses the design and manufacture of a fuel flow simulator for an aircraft fuel system using LED lights as a substitute for fuel. This final project aims to design and create a fuel flow simulator for an aircraft fuel system as an alternative learning medium. There are two methods used in completing this Final Project, namely analytical and experimental methods which consist of several stages including problem identification, data collection, tool design, tool design, and tool testing.The results showed that with the Design and Build of the Electronic-Based Cessna 172 Aircraft Fuel System Simulator, where the value of cadets when learning using simulation tools has increased compared to without using tools. Itcan be concluded that this fuel system simulation tool can scientifically increasethe value and understanding of cadets, especially material about fuel systems.